A case for low-latency communication layer for distributed operating systems - Kim, Sang Hoon (IEICE Transactions on Information and Systems, 2021)
There have been increasing demands for distributed operating systems to better utilize scattered resources over multiple nodes. This paper enlightens the challenges and requirements for the communication layers for distributed operating systems, and makes a case for a versatile, high-performance communication layer over InfiniBand network.
Keywords: Communication layers; Distributed operating systems; High performance communication; Infiniband; InfiniBand networks; Low-latency communication; Multiple nodes; RPC; Scattered resources; Distributed operating systems; InfiniBand; RPC